Kearifan Lokal Pengelolaan Hutan Adat oleh Masyarakat Adat Tigo Luhah Kemantan Kabupaten Kerinci - Lensi Erika Novianti; Hamzah Hamzah; Bambang Hariyadi (Universitas Batanghari Jambi, 2022)
This study aims to describe and identify local wisdom in the management of the Tigo Luhah Kemantan Customary Forest (HATLK) from the aspect of forest management elements (planning, organizing, actuating, controlling or POAC). HATLK is one of the customary forests in Kerinci Regency which has very good forest conditions. One of the problems or obstacles in the management of HATLK is the influence of modernization or the entry of a new culture in the HATLK community. The type of data used in this study consisted of primary data and secondary data. Primary data was obtained from qualitative data directly at the research site, through in-depth interviews with informants, then along with observation and documentation of research activities. Secondary data is obtained through books, archives, reports, publications from the government/private sector, census results, journals and others that support primary data. Based on the results obtained by the local wisdom of the Six Villages of Kemantan in the management of HATLK, apart from the cooperation of the community in forming customary forest management, it is also inseparable from the important role of customary institutions, because for the people of Kemantan, customary institutions are the highest institutions that regulate and supervise human interaction. with the environment. These traditional institutions are the Depati, Pemangku, Ninik Mamak/Pateh/Rio, and Hulubalang, which have their respective roles and functions. Characteristics The local wisdom of the indigenous peoples of the Six Kemantan Villages in HATLK Management is manifested in the form of trust, and customary law which contains applicable norms and rules, so that if these norms and rules are violated, they will get sanctions.